Jazz/Not Jazz : The Music and Its Boundaries - Goldmark, Daniel; Garrett, Charles Hiroshi, 1966-; Ake, David Andrew, 1961- (Book collections on Project MUSE., 2012)
What is jazz? What is gained--and what is lost--when various communities close ranks around a particular definition of this quintessentially American music? Jazz/Not Jazz explores some of the musicians, concepts, places, and practices which, while deeply connected to established jazz institutions and aesthetics, have rarely appeared in traditional histories of the form. David Ake, Charles Hiroshi Garrett, and Daniel Goldmark have assembled a stellar group of writers to look beyond the canon of acknowledged jazz greats and address some of the big questions facing jazz today.